Natural biological control of the citrus swallowtail [Papilio] by r-selected parasitoids [in Japan] - Hirose, Y. (Penerbit Universiti Pertanian Malaysia, 2013)
The citrus swallowtail, Papilio xuthus Line, is a pest of young citrus trees in Japan, but it never reaches outbreak level and its population is usually maintained at a low level. A life-table study conducted in a suburban area of Fukuoka, Japan, showed that the pest population was spatially and temporally regulated by the egg parasitoids, Trichogramma spp. (mainly T. papilionis Nagarkatti) and the pupal parasitoid, Pteromalus puparum (Linne). The reasons for such a naturally-occurring biological control in existence was explained by the following facts (i) these parasitoids were selected species exhibiting a high reproductive potential due to a short generation time, (ii) the eggs and pupae of the multivoltine host were almost present through its long growing season, affording opportunity for continuous parasitoid activity and (iii) the host of natural biological control, classical biological control of pests by selected parasitoids was discussed. Problems of the detection of density-dependent regulation by natural enemies were also discussed